Pancreatic fat content assessed by 1H magnetic resonance spectroscopy is correlated with insulin resistance, but not with insulin secretion, in Japanese individuals with normal glucose tolerance. Issue 3 (14th September 2017) - Komada, Hisako; Sakaguchi, Kazuhiko; Hirota, Yushi; Sou, Anna; Nakamura, Tomoaki; Kyotani, Katsusuke; Kawamitsu, Hideaki; Sugimura, Kazuro; Okuno, Yoko; Ogawa, Wataru
Abstract: Aims/Introduction: Whereas some clinical studies have shown that excessive fat accumulation in the pancreas is associated with impairment of insulin secretion, others have not found such an association. 1 H magnetic resonance spectroscopy allows quantitative fat analysis in various tissues including the pancreas. The pathological relevance of pancreatic fat content (PFC) in Japanese individuals remains unclear, however. Materials and Methods: We analyzed PFC in 30 Japanese individuals with normal glucose tolerance by 1 H magnetic resonance spectroscopy, and then investigated the relationships between PFC and indexes of insulin secretion and insulin sensitivity‐resistance determined by an oral glucose tolerance test. We also measured hepatic fat content and intramyocellular lipid content by 1 H magnetic resonance spectroscopy, as well as visceral fat area and subcutaneous fat area by magnetic resonance imaging, and we examined the relationships between these fat content measures and oral glucose tolerance test‐derived parameters. Results: PFC was correlated with indexes of insulin sensitivity‐resistance, but not with those of insulin secretion. Hepatic fat content and visceral fat area were correlated with similar sets of parameters as was PFC, whereas subcutaneous fat area was correlated with parameters of insulin secretion, and intramyocellular lipid content was not correlated with any of the measured parameters. The correlation between PFC and homeostasis model assessment of insulin resistance remained significant after adjustment for age, body mass index and sex. Among fat content measures, PFC was most highly correlated with hepatic fat content and visceral fat area. Conclusions: PFC was correlated with indexes of insulin resistance, but not with those of insulin secretion in non‐obese Japanese individuals with normal glucose tolerance. Abstract : Pancreatic fat content, obtained from Magnetic Resonance Spectroscopy, was correlated with indexes of insulin resistance but not with those of insulin secretion in nonobese Japanese subjects with normal glucose tolerance.